Impact of Integrated Weed Management on Bulb Yield of Onion - Islam, MR; Moniruzzaman, M; Obaidullah, AJM; Fahim, AHF (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Regional Spices Research Centre, Bangladesh Agricultural Research Institute, Magura, Bangladesh during 2016-2017 and 2017- 2018 to optimize weed management practice for onion bulb production through Integrated Weed Management (IWM). The experiment was laid out in a Randomized Complete Block Design with three replications. Two different herbicides (Oxadiazon and Pendimethalin) with different doses in combination with hand weeding (HW) were used as treatments. The total number of treatments were 12 viz. T1=Oxadiazon@1.0 l/ha, T2=Oxadiazon@1.5 l/ha, T3= Oxadiazon@2.0 l/ha, T4= Oxadiazon@1.0 l/ha + one HW at 45 DAT (Days After Transplanting), T5= Oxadiazon@1.5 l/ha + one HW at 45 DAT,T6= Oxadiazon@2.0 l/ha + one HW at 45 DAT, T7=Pendimethalin@1.0 l/ha, T8=Pendimethalin@1.5 l/ha, T9= Pendimethalin@1.0 l/ha + HW at 45 DAT, T10= Pendimethalin@1.5 l/ha+ HW at 45 DAT, T11= Weed free and T12 = Weedy check (control). The onion var. BARI Piaz-1 was used as the test crop. The highest bulb yield (7.63 tha-1 in 2016 & 9.56 t ha-1in 2017) and benefit cost ratio (2.14 in 2016 and 2.46 in 2017) were obtained from T6= Oxadiazon@2.0 l/ha + one hand weeding at 45 DAT while the lowest bulb yield (4.22 t ha-1in 2016 and 6.28 t ha-1in 2017) was obtained from T12 = Weedy check (control), while lowest benefit cost ratio (1.33 in 2016 and 1.74 in 2017) from treatment T11 =Weed free. It was concluded that Oxadiazon@2.0 l/ha with one hand weeding at 45 days after transplanting performed better for controlling weed and maximizing bulb yield of onion. Bangladesh Agron. J. 2020, 23(1): 83-89